2022
DOI: 10.3390/fermentation8080390
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the Microbiological and Physicochemical Properties of Bio-Frozen Yoghurt Made with Probiotic Strains in Combination with Jerusalem Artichoke Tubers Powder

Abstract: Frozen yoghurt is a refreshing and nutritious dessert, with or without the flavour that combines the texture of ice cream and yoghurt. Several previous studies have been conducted on Jerusalem artichoke tubers due to their components, which contain inulin compounds and other nutrients with beneficial properties of fresh yoghurt. However, limited studies explored the potential benefits of the addition of Jerusalem artichoke tuber powder as a fat replacer on the physicochemical properties and survival of probiot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 35 publications
1
10
0
Order By: Relevance
“…These products were well accepted by consumers. Shahein et al [ 21 ] evaluated the microbiological and physicochemical characteristics of frozen yoghurt made with probiotic strains in combination with Jerusalem artichoke tubers powder (JATP) used as a fat and sugar replacer. Samples with JATP contained viable counts of Bifidobacterium bifidum BGN4 and Lactobacillus casei Lc-01 of 7 log CFU/g during 90 days of storage, as compared to the control sample.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These products were well accepted by consumers. Shahein et al [ 21 ] evaluated the microbiological and physicochemical characteristics of frozen yoghurt made with probiotic strains in combination with Jerusalem artichoke tubers powder (JATP) used as a fat and sugar replacer. Samples with JATP contained viable counts of Bifidobacterium bifidum BGN4 and Lactobacillus casei Lc-01 of 7 log CFU/g during 90 days of storage, as compared to the control sample.…”
Section: Resultsmentioning
confidence: 99%
“…The production of frozen yoghurts or ice creams with low fat or lactose levels and/or with added prebiotics and probiotics created new opportunities for the development of dairy foods with health-promoting properties. An increasing number of papers describe the formulations and characteristics of such products [ 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 ]. The production of ovine’s and caprine’s yoghurts and frozen yoghurts has also followed this trend.…”
Section: Introductionmentioning
confidence: 99%
“…Fortifications of dairy products with natural substances enhance the physicochemical characterizations and nutritive values of functional food, and therefore, have attracted many research projects over the last few decades [21][22][23][24][25][26][27][28][29]. Many studies reported that herbal therapy is considered an effective way to the management of diabetes.…”
Section: Introductionmentioning
confidence: 99%
“…The preferred pH and acidity of frozen yoghurt were 4.65 and 0.78% lactic acid (LA), respectively (Shahein et al . 2022).…”
Section: Introductionmentioning
confidence: 99%